Four decades of scientific explanation - Salmon, Wesley C. (University of Pittsburgh Press Digital Editions., 2006)
Provides an account of the developments in scientific explanation that transpired in the last four decades of the twentieth century. This book underscores the need for a consensus of approach and evaluations of methodology in scientific explanation, withthe goal of providing an understanding of natural phenomena.